Estimating the Ground and Excited State Dipole Moments of Levofloxacin and Norfloxacin Drugs Using Solvatochromic Effects and Computational Work - Woldegiorges, Kinfe; Belay, Abebe; Kebede, Alemu; Abebe, Tamirat (Journal of Spectroscopy, 2021)
Levofloxacin (LVF) and norfloxacin (NRF) are a group of fluoroquinolone antibiotics, broad spectrum used to treat various infections caused by many bacterial species. The drugs contain functional groups which control the type and degree of interaction with different solvents. In this research, the ground and excited state dipole moments of LVF and NRF drugs were estimated using solvatochromic effects and computational work. The dipole moments were estimated from absorption and emission spectra in polar and nonpolar solvents using Bakhshiev’s, Kawski–Chamma–Viallet, Lippert–Mataga, and Reichardt models. The results indicated the emission spectra are more strongly affected by solvent polarity than the absorption spectra. The calculated excited state dipole moment is larger than that of the ground state, indicating that the probe compounds are significantly more polarized in the excited state than in the ground state. From computational work, the HOMO-LUMO energy band gap, the dipole moments, electron charge density distribution, and oscillator strength were determined using the semiempirical MP6 method, DFT-B3LYP-6-31G, and DFT-B3LYP-3-21G employing Gaussian 09 software. In general, larger dipole moments were obtained by computation rather than from experiments due to the absence of solvent effects.